Radioprotective Effect of Aminothiol PrC-210 on Irradiated Inner Ear of Guinea Pig - Giese, Arnaud P. J.; Guarnaschelli, Jess G.; Ward, Jonette A.; Choo, Daniel I.; Riazuddin, Saima; Ahmed, Zubair M. (PLOS ONE, 2015)
Radiotherapy of individuals suffering with head & neck or brain tumors subserve the risk of sensorineural hearing loss. Here, we evaluated the protective effect of Aminothiol PrC-210 (3-(methyl-amino)-2-((methylamino)methyl)propane-1-thiol) on the irradiated inner ear of guinea pigs. An intra-peritoneal or intra-tympanic dose of PrC-210 was administered prior to receiving a dose of gamma radiation (3000 cGy) to each ear. Auditory Brainstem Responses (ABRs) were recorded one week and two weeks after the radiation and compared with the sham animal group. ABR thresholds of guinea pigs that received an intra-peritoneal dose of PrC-210 were significantly better compared to the non-treated, control animals at one week post-radiation. Morphologic analysis of the inner ear revealed significant inflammation and degeneration of the spiral ganglion in the irradiated animals not treated with PrC-210. In contrast, when treated with PrC-210 the radiation effect and injury to the spiral ganglion was significantly alleviated. PrC-210 had no apparent cytotoxic effect in vivo and did not affect the morphology or count of cochlear hair cells. These findings suggest that aminothiol PrC-210 attenuated radiation-induced cochlea damage for at least one week and protected hearing.